The double-edged nature of Neil Gaiman’s irоnical perspectives and liminal fantasies - Sh. K. Sadiyeva (International Journal on Orange Technologies, 2021)
Intertextuality as an important issue while learning Neil Gaiman’s works. Thus, it refers to other fictions by its characters, scenery, plot or the process of the events. In this piece, the double-edged features of the author’s work are discussed within the luminal fantasies. In double-edged natures of the work, the outcomes may come possible and two contrast ideas or a logical incompatibility among two or more elements come as predictable solution or ending.